Future skills for professionals: get clarity amidst complex needs and priorities - Scaglione, Amanda; Birt, Brad; Pridmore, Beth (Curtin University, 2020)
To thrive amidst the changing world of work Australian professionals will need to develop new skills and capabilities. Curtin engaged professionals across a range of industries to understand their upskilling needs and preferences. This report summarizes survey responses from professionals in the context of global dynamics and Western Australia’s economy. This report highlights key insights to guide those responsible for organisational and professional development across six future skill areas: Innovation, Cognitive Flexibility, Effective Work Design, Personal Leadership, Industry 4.0 Technologies, and Global Sustainability.